Arranjo espacial de plantas na cultura do pinhão manso em Selvíria (MS) - Daniel, Henrique [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The new orientation of energy agriculture is to produce raw materials for biodiesel, and one of the alternatives, Jatropha grains. To obtain information about the culture, developed this study to evaluate the vegetative growth, yield of Jatropha grains and Total Operating Cost in the first year after planting, depending on spatial arrangements between plants. The experiment was conducted in the experimental area of UNESP - Ilha Solteira Campus, located in Selvíria County, Mato Grosso do Sul State, Brazil,in the period from 04/09/2010 to 07/27/2011. We used a randomized block design, with 17 treatments and 4 replications. The spacing between rows and between plants used were, respectively: 2.0x1.0, 2.0x1.5, 2.0x2.0, 3.0x1.0, 3.0x1.5, 3.0x2.0, 3.0x3.0, 4.0x1.0, 4.0x1.5, 4.0x2.0, 4.0x3.0, 4.0x4.0, 5.0x1.0, 5.0x1.5, 5.0x2.0, 5.0x3.0 and 5.0x4.0 m. It was done 7 evaluations on plants phenology of fruit and 3 harvests. Jatropha plants had an average height of 2.26 m, stem diameter of 101 mm, 6 branches per plant, six inflorescences, four clusters, the average canopy diameter of 2.06 m and the avarage closure of street was 60%. Treatments did not influence the relationship peel/fruit that average was 31.3 wt%. The most dense spacing, 2.0x1.0, 3.0x1.0 and 3.0x1.5 m, were the most productive, with yield of 821, 887 and 1.027 kg ha -1 , respectively. The Total Operating Cost in the crop establishment, spaced 3,0x1,0 m was R$ 6,751.34 ha -1 and spacing of 4.0x4.0 m was R$ 3,154.43 ha -1 , while driving in 1 st year was R$ 4,945.19 ha -1 and R$ 4,097.17 ha -1 , respectively

A nova orientação da agricultura energética é no sentido de produzir matérias primas para o biodiesel, sendo uma das alternativas, grãos de pinhão manso (Jatrophacurcas L.). Visando obter mais informações sobre a cultura, desenvolveu-se o presente trabalho objetivando avaliar o desenvolvimento vegetativo, a produtividade de grãos de pinhão manso e o Custo Operacional Total, no primeiro ano após o plantio, em função de arranjos espaciais entre plantas. O experimento foi desenvolvido na área experimental da UNESP - Campus de Ilha Solteira, localizada em Selvíria - MS, no período de 09/04/2010 a 27/07/2011. Utilizou- se o delineamento experimental em blocos casualizados, com 17 tratamentos e 4 repetições. Os espaçamentos entre linhas e entre plantas na linha utilizados foram, respectivamente: 2,0x1,0, 2,0x1,5, 2,0x2,0, 3,0x1,0, 3,0x1,5, 3,0x2,0, 3,0x3,0, 4,0x1,0, 4,0x1,5, 4,0x2,0, 4,0x3,0, 4,0x4,0, 5,0x1,0, 5,0x1,5, 5,0x2,0, 5,0x3,0 e 5,0x4,0 m. Foram realizadas 7 avaliações fenológicas nas plantas e 3 colheitas dos frutos. As plantas de pinhão manso apresentaram altura média de 2,26 m, diâmetro de caule de 101 mm, 6 ramos por planta, 6 inflorescências, 4 infrutescências, diâmetro médio da copa de 2,06 m e o fechamento médio da rua foi de 60%. Os tratamentos não influenciaram na relação casca/fruto que em média foi de 31,3% em peso. Os arranjos mais adensados de 2,0x1,0, 3,0x1,0 e 3,0x1,5 m foram os mais produtivos, com produtividade de 821, 887 e 1.027 kg ha -1 , respectivamente. O Custo Operacional Total na implantação da lavoura, no arranjo de 3,0x1,0 m foi de R$ 6.751,34 ha -1 e no arranjo 4,0x4,0 m foi de R$ 3.154,43 ha -1 , enquanto que na condução do 1o ano, foi de R$ 4.945,19 ha -1 e R$ 4.097,17 ha -1 , respectivamente
Keywords: Pinhão-manso - Espaçamento; Crescimento (Plantas); Produtividade agrícola; Plantas - População; Biodiesel; Biodiesel fuels